Content Learning in an Interprofessional Environment for Health and Social Care Students: The Role of Learning Activities and Group Work Appraisals - Erika Österholm; Tuike Iiskala; Minna-Kaarina Wuorela; Outi Kortekangas-Savolainen; Mari Murtonen (MDPI AG, 2023)
Undergraduate interprofessional courses aim to enhance health and social care students' knowledge and skills for working life. Employing a pre-posttest design, this mixed methods study explored the impact of a new interprofessional course on content learning with the aid of mind maps. Questionnaires were used to assess the course's effect on learning activities (including strategies for cognitive processing and regulation) and appraisals of group work. The students represented six health and social care disciplines. The results indicate that students' content learning at the concept level was significantly improved. While participants' cognitive, critical processing was clearly enhanced and group work appraisals became more positive, more than one in four post-course mind maps overlooked an essential concept related to interprofessional work. The more sophisticated mind maps were linked to a stepwise cognitive processing strategy and a sense of the cognitive benefits of group learning. This relatively short course did not impact regulation strategies. The study discusses the implications of these findings for effective techniques to support interprofessional learning in higher education.